Exploring property-structure-performance relationship for additive manufactured Ti-6Al-4V alloy through experimental studies - Gupta, Alok (2023)
Additive Manufacturing (AM) offers design freedom and ability to fabricate parts of complex shapes which are not often possible with the conventional methods of manufacturing. AM has gained a widespread attention within the aerospace and bio-medical industries to make parts in Ti-6Al-4V, an α + β alloy. A thorough understanding of the relationship between the AM process, microstructure, mechanical and fatigue properties, and performance of AM parts is therefore critical to establish AM as an alternative and preferred route to manufacture safety critical parts. The AM components designed for aerospace applications need to be compliant against the certification requirements of EASA (e.g. CS-E 650, CS-E 810 and CS-E100). Therefore, the main purpose of this research study was to verify that the carefully designed weight optimised AM bracket meets the targeted fatigue performances under LCF and HCF loadings to be in line with the aerospace standards and to build confidence amongst the practicing engineers, researchers and certification authorities to adopt this novel technology for safety critical applications such as the aerospace. To achieve this objective, the main focus of the present study was thus to analyse the mechanical and fatigue properties of Powder Bed Fusion Ti-6Al-4V through a series of experiments performed at specimen and component levels, and to evaluate the effect of characteristic microstructure, defects, surface roughness, micro-hardness and characteristic features present on the fracture surfaces of the specimen and component, on these properties. Firstly, the tensile behaviour of Ti-6Al-4V was studied for both Electron Beam Powder Bed Fusion (EPBF) and Laser Powder Bed Fusion processes (LPBF), at Room Temperature (RT) and at Elevated Temperatures (ETs), and at two different strain rates. The characterisation of defects and its role in relation to the mechanical strength of the EPBF and LPBF Ti-6Al-4V has also been presented. Further, for the first time, this research presents a detailed investigation on the Low Cycle Fatigue (LCF) and High Cycle Fatigue (HCF) performances of an aero-engine LPBF Ti-6Al-4V bracket in struts and connectors design. The novel bracket design was tested for its fatigue performance which was evaluated in relation to the fatigue behaviour of LPBF Ti-6Al-4V, tested at RT and at ETs. Additionally, the cyclic softening behaviour seen during the LCF testing of LPBF Ti-6Al-4V was studied in detail to understand and identify the micro-mechanisms responsible for cyclic softening. The features of fracture surface and evolution of microstructure and dislocation density near the fracture surface have also been discussed. For machined EPBF Ti-6Al-4V, decrease in tensile strengths but increase in material ductility were observed for the tests at ETs on machined specimens. The poor surface finish of the as-built specimen and presence of defects are the two significant contributors to reduce material ductility of as-built EPBF Ti-6Al-4V at ETs. Furthermore, the tensile strengths of LPBF Ti-6Al-4V were higher, owing to its fine microstructure with α’ needles in high aspect ratio, but the ductility was lower than the EPBF Ti-6Al-4V. Orientation of defects and columnar β grains in the microstructure of PBF Ti-6Al-4V causes anisotropy in material properties. During cyclic deformation, formation of Low Angle Boundaries inside the prior α’ grains, progressively leads to nucleation and eventually to fracture. With increase in fatigue cycles, the free dislocation density increases resulting into cyclic softening of LPBF Ti-6Al-4V. It was found that the bracket in struts and connectors design for aerospace application has redundancies in the load paths due to its particular design and it meets the set performance targets, in terms of number of cycles to failure and its g capability against the LCF and HCF test loading conditions, respectively. Finally, a fatigue crack growth life prediction method which considers the small crack growth behaviour, has also been proposed. The proposed method includes a Finite Element based crack growth simulation and the calculations utilise an approach based on the modified NASGRO equation.